Alterations of NURR1 and Cytokines in the Peripheral Blood Mononuclear Cells: Combined Biomarkers for Parkinson’s Disease - Li, Tianbai; Yang, Zhaofei; Li, Song; Cheng, Cheng; Shen, Bairong; Le, Weidong (Frontiers in Aging Neuroscience, 2018)
Nuclear receptor related 1 protein (NURR1), a transcription factor as key player for maintaining dopamine neuron functions and regulating neuroinflammation in the central nerves system, is a potential susceptibility gene for Parkinson’s disease (PD). To ascertain whether the expression levels of NURR1 gene and inflammatory cytokines are altered in patients with PD, we measured their mRNA levels in the peripheral blood mononuclear cells (PBMCs) in 312 PD patients, 318 healthy controls (HC), and 332 non-PD neurological disease controls (NDC) by quantitative real-time PCR. Our data showed that NURR1 gene expression was significantly decreased in the PBMCs of PD as compared with that of HC and NDC (p < 0.01). Since NURR1 was reported to have regulating effects on neuroinflammation, we assessed the expression levels of cytokines (TNF-α, IL-1β, IL-4, IL-6 and IL-10) in the PBMCs of PD and controls (HC and NDC). Our results showed that the expression levels of those cytokines were significantly higher than those of controls. Statistical analysis revealed that NURR1 expression presented a negative correlation with the expression of TNF-α, IL-1β, IL-6 and IL-10, and collectively the measurements of NURR1 plus those cytokines significantly improve the diagnostic accuracy. All these findings suggested that NURR1 is likely to be involved in the process of PD by mediating the neuroinflammation, and the combination of NURR1 and cytokines assessment in the PBMCs can be potential biomarkers for PD diagnosis.